An approach towards sustainable renovation—A tool for decision support in early project stages. (September 2016) - Olsson, Stefan; Malmqvist, Tove; Glaumann, Mauritz
Abstract: Reducing greenhouse gas (GHG) emissions through energy reduction in buildings is a high priority for policy-makers in the European Union and elsewhere. However, although long-term sustainability targets exist on the societal level, it is not obvious how these targets may trickle down to individual sectors and further down to specific organizations or buildings. The aim of this paper is to illustrate an approach for evaluating renovation measures in order to identify appropriate target levels in early project stages and what is needed to achieve a number of proposed sustainability targets. The evaluation approach is supported by a tool that can be seen as an aid to making rough estimations of the environmental impacts. Sustainability target levels in a Swedish context are presented for three issues: operational energy use, GHG emissions due to total energy use for building operation, and embodied GHG emissions due to production of materials. The approach to support well-grounded retrofit decisions is shown with a case study. The tool developed, in combination with a suggested step-by-step evaluation approach, provides an effective way to evaluate various potential improvements, and their consequences, in early project stages. However, other tools with similar functionality may be used. Results from the case illustration imply that it is possible to achieve the proposed sustainability targets for operational energy use by implementing nine measures. However, the targets for GHG emissions for operational energy use and embodied GHG emissions were not achieved because of an energy supply with too high a share of non-renewable fuels. Abstract : Present a procedure to evaluate building improvements in early project stages. Identifies target levels for three important sustainability aspects. Demonstrate the evaluation procedure and sustainability targets with a case study. Shows the difficulty to achieve targets like GHG emission due to operational energy. Despite significantly reduced energy demand, the need for more renewable fuels are shown.